A cohort study on the correlation between serum Klotho levels and all-cause mortality in American diabetic populations - Kangxiang Wu; Jiaqi Chen; Yiying Lin; Jie Wang (Diabetology & Metabolic Syndrome)
Abstract Background The global prevalence of diabetes is on an upward trajectory. The management of complications related to the condition has seen limited progress in recent years. Klotho, characterized as an anti-aging protein that mitigates oxidative stress and inflammation, has previously been correlated with all-cause mortality in the broader United States population. The objective of this research was to investigate the persistence of this relationship among diabetic patients. Methods This study meticulously analyzed data (2007–2016) sourced from the National Health and Nutrition Examination Survey, encompassing a cohort of 3,560 individuals. To elucidate the links of Klotho with all-cause mortality in diabetic patients, a multivariate Cox proportional hazards regression model was employed. The relationship was further explored using the restricted cubic spline model, threshold analysis, and subgroup analysis. Additionally, a mediation analysis was conducted to unravel the influence of age on the observed correlations. Results Throughout the observation period, which had a median duration of 84 months, the incidence of all-cause mortality reached 18.511%. The Cox model analysis revealed a statistically significant association between Klotho levels and all-cause mortality. Further, the application of restricted cubic splines revealed a nuanced, nonlinear relationship between exposure factors and outcome across the entire study population (nonlinear P < 0.001), pinpointing a critical threshold at 829.138 pg/mL. Subgroup analyses showed consistent correlation between Klotho levels and mortality across various groups. Intriguingly, mediation analysis indicated that age was a significant mediator, accounting for 76.1% of the observed correlation of Klotho levels with all-cause mortality among diabetic patients. Conclusions Low levels of Klotho were found to be strongly associated with an increased risk of all-cause mortality in individuals with diabetes (Klotho levels < 829.138 pg/ml), and a nonlinear relationship was observed between these two variables. These associations were largely mediated by age.